Insufficient vaccination and inadequate immunization rates among Korean patients with inflammatory bowel diseases. Issue 45 (12th November 2021) - Ryu, Han Hee; Chang, Kiju; Kim, Nayoung; Lee, Ho-Su; Hwang, Sung Wook; Park, Sang Hyoung; Yang, Dong-Hoon; Byeon, Jeong-Sik; Myung, Seung-Jae; Yang, Suk-Kyun; Ye, Byong Duk
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: This study aimed to evaluate self-reported vaccination rates, immunity, knowledge of and attitudes toward vaccination among Korean patients with inflammatory bowel disease (IBD) as well as to identify factors associated with proper vaccination. Between November 2013 and February 2015, consecutive patients with IBD were invited to complete a standardized questionnaire on vaccination. Moreover, immune status for common vaccine-preventable diseases was evaluated via serologic tests. A total of 310 patients with IBD were invited to the questionnaire survey and 287 patients (92.6%) who completed the questionnaires were finally enrolled (men, 188 [65.5%], median age at survey, 29.9 years [interquartile range, 22.3–39.2], ulcerative colitis: Crohn disease = 165:122]. Self-reported vaccine uptake rates were as follows: hepatitis A virus (HAV; 13.2%), hepatitis B virus (HBV; 35.2%), seasonal influenza (43.2%), pneumococcus (4.9%). Most of the patients (87.1%) did not know that proper vaccination has been recommended for patients with IBD. Up to 64.8% and 32.8% of patients were negative for IgG anti-HAV antibody and IgG HBV surface antibody, respectively. In a multivariable analysis, newspaper subscription (aOR [adjusted odds ratio] 2.185, 95% confidence interval [CI] 1.136–4.203, P = .019), ever recommendation of vaccination by a physician (aOR 2.456, 95% CI 1.240–4.862, P = .010), and use of anti-tumor necrosis factor agents (aOR 4.966, 95% CI 1.098–22.464, P = .037) showed a significant association with uptake of adult vaccines recommended for patients with IBD. Vaccine uptake rates, positivity of antibody to HAV and HBV, and knowledge of patients with IBD regarding vaccination were not sufficient. Proper educational information and recommendation from physicians could enhance awareness among patients with IBD about the need for vaccination and thereby improve vaccination rates. Trial registration number: NCT01984879.